2013
DOI: 10.1177/1057083713502731
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration as Effective Music Professional Development

Abstract: Collaborative professional development (PD) efforts are increasingly popular and successful across the United States. In this article, we highlight the voice of the teacher in brief descriptions of PD efforts that support collaboration as a key component of meaningful music teacher PD. To draw a vivid picture of the potential and possibilities in models of music teacher collaborative PD, we connect eight practicing teachers’ positive PD experiences to recommendations from recent research findings. We also make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…The theme of collaboration with peers as a way to increase the effectiveness of professional development and also as a possible solution to isolation has been an area of interest to those in music education research. While a number of researchers have focused on the topic of collaboration as a means to make professional development more successful and meaningful (Gruenhagen, 2009;Hammel, 2007;Kastner, 2012;Monsour, 1991;Pellagrino, 2011;Pelletier, 2013;Stanley, 2012;Stanley, Snell, & Edgar, 2014), fewer have considered the long-term benefits that collaboration could play with helping ease feelings of isolation (Sindberg & Lipscomb, 2005). There is further evidence that informal, rather than formal, collaboration among music teachers might be the most valuable form of professional development (Conway, 2008), but both forms of professional development are shown to have value (Eros, 2013;Pelletier, 2013).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The theme of collaboration with peers as a way to increase the effectiveness of professional development and also as a possible solution to isolation has been an area of interest to those in music education research. While a number of researchers have focused on the topic of collaboration as a means to make professional development more successful and meaningful (Gruenhagen, 2009;Hammel, 2007;Kastner, 2012;Monsour, 1991;Pellagrino, 2011;Pelletier, 2013;Stanley, 2012;Stanley, Snell, & Edgar, 2014), fewer have considered the long-term benefits that collaboration could play with helping ease feelings of isolation (Sindberg & Lipscomb, 2005). There is further evidence that informal, rather than formal, collaboration among music teachers might be the most valuable form of professional development (Conway, 2008), but both forms of professional development are shown to have value (Eros, 2013;Pelletier, 2013).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Effective PD in the arts, vocational education, and elementary and high schools includes components of collaboration and active learning (Abilock, Harada, & Fontichiaro, 2013;Shoulders & Myers, 2014;Stanley, Snell, & Edgar, 2014;Wallace, 2014). Mishkind (2014) found duration as the key factor in evidence-based professional learning, while Darling-Hammond and Richardson (2009) identified content, context, and design as the characteristics of effective professional development.…”
Section: The Literaturementioning
confidence: 99%
“…Many music education scholars have examined music teacher professional development to discover what qualities make it most relevant and beneficial (e.g., Bauer, 2007; Conway, 2007, 2008, 2011; Stanley, 2011). Music teachers and researchers have agreed that content-specific professional development is best (Ballantyne, 2007; Bauer, Forsythe, & Kinney, 2009; Burkett, 2011; Conway, 2008, 2011; Conway, Hibbard, Albert, & Hourigan, 2005; Hourigan, 2011; Pellegrino, 2011; Scheib, 2006; Stanley, 2011; Stanley, Snell, & Edgar, 2014). Burkett (2011) found that instrumental music teachers valued subject-specific professional development and appreciated using materials from their classrooms as content because it was meaningful and relevant to their teaching situations.…”
mentioning
confidence: 99%